Recommendations from treatment guidelines for schizophrenia regarding monitoring of side effects of antipsychotics : brief review (Array, 2009)
The objective of this paper is to review therapeutic ways of management of antipsychotics side effects. In order to obtain this, modern guidelines were investigated, as well as recent articles on this subject. Guidelines recommend that side effects should be monitored regularly, and the side effect profile of the prescribed antipsychotic should be considered. In case of unacceptable side effects, changing to a different antipsychotic is recommended.